Radar absorbing Films Based on Chitosan–Polyvinyl Alcohol Incorporated with Hydroxyapatite from Yellowfin Tuna Bone Waste - Fran Denis Sitohang; Muhammad Hibban Fadlurrohman Ayyasy; Esa Ghanim Fadhallah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Radar absorbing films (RAF) play a crucial role in stealth technology by reducing radar reflections and thereby lowering the detectability of objects. Conventional inorganic absorbers such as ferrite and carbon are effective but present limitations due to their high density, cost, and limited environmental compatibility. These challenges have driven interest in developing lightweight, sustainable, and polymer-based alternatives. Yellowfin tuna bone waste, containing approximately 60–70% minerals predominantly composed of hydroxyapatite, offers a promising source for enhancing electromagnetic absorption while simultaneously supporting waste valorization. This study aimed to evaluate the mechanical and electromagnetic properties of RAF from chitosan, polyvinyl alcohol (PVA), and hydroxyapatite derived from yellowfin tuna bone waste. The films were produced with varying chitosan concentrations (0%, 0.5%, 1%, 1.5%, 2%) and characterized for tensile strength, elongation, stiffness, and electromagnetic absorption across the 5–10 GHz frequency range. The tensile strength increased from 0.105 MPa in the control to 0.151 MPa at 2% chitosan, while elongation declined from 39% at 0.5% chitosan to 21% at 1.5% chitosan. The optimal absorption was observed at 1.5% chitosan, exhibiting a reflection loss of 14 dB at 8 GHz, which corresponds to approximately 96% absorption with only 4% reflection. Overall, the films demonstrated a favorable balance between mechanical integrity and electromagnetic wave absorption, highlighting their potential as lightweight, flexible, and environmentally sustainable radar absorbing materials.